Intraoperative goal‐directed hemodynamic management in free tissue transfer for head and neck cancer. (1st February 2016) - Hand, William R.; Stoll, William D.; McEvoy, Matthew D.; McSwain, Julie R.; Sealy, Clark D.; Skoner, Judith M.; Hornig, Joshua D.; Tennant, Paul A.; Wolf, Bethany; Day, Terry A.
Abstract: Background: The purpose of this study was to determine the effect of algorithmic physiologic management on patients undergoing head and neck free tissue transfer and reconstruction. Methods: Ninety‐four adult patients were randomized to treatment and control groups. The blood pressure of the control group was managed consistent with contemporary standards. The treatment group was managed using an algorithm based on blood pressure and calculated physiologic values derived from arterial waveform analysis. Primary outcome was intensive care unit (ICU) length of stay. Results: ICU length of stay was decreased in the treatment group (33.7 vs 58.3 hours; p = .026). The complication rate was not increased in the treatment group. Conclusion: The goal‐directed hemodynamic management algorithm decreased the ICU length of stay. Judicious use of vasoactive drugs and goal‐directed fluid administration has a role in improving perioperative outcomes for patients undergoing head and neck free tissue transfer. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E1974–E1980, 2016